Exploitable genetic variability and determination of selection criteria using path coefficient analysis in chickpea (Bangladesh Journal of Botany, 2015)
This study estimates the nature and extent of genetic variability as well as direct and indirect effects of yield related traits on seed yield in 25 chickpea genotypes. The pooled analysis of variance over the environments indicated significant genotypes effect compared to genotype (g) × environment (e) interactions for all the characters. The mean values of the characters studied showed a wide spectrum of genetic variation. The genotypes ICCV 96904 and Himachal Chana-1 were found to be promising for seed yield and biological yield per plant in pooled over the environments. The phenotypic correlation coefficient revealed significant positive associations of pods per plant, harvest index, biological yield per plant and primary branches per plant with seed yield per plant. The path coefficient analysis revealed that biological yield per plant and harvest index exhibited positive and high direct effects on seed yield per plant. Therefore, these characters could be considered as the best selection parameters for the improvement of seed yield per plant. DOI: http://dx.doi.org/10.3329/bjb.v44i1.22737 Bangladesh J. Bot. 44(1): 139-142, 2015 (March)